The effect of insects on leather artifacts in museums and ways to reduce them - rezzik, Abd ar-Rahmân (The Algerian Historical Journal, 2026)
The study highlights the impact of insects on leather artifacts by clarifying their types, factors of their entry into museums and their development, and treating their presence by diagnosing and removing them, and how to deal with and protect against them. We explain the most important materials and techniques for catching, diagnosing and exterminating them. As a result, it became clear that insects are one of the most dangerous factors of damage, as they are a nutrient that they eat, or for laying eggs and larvae and their reproduction and affecting their secretions. Therefore, they must be eliminated using practical methods and advanced techniques that achieve the appropriate preservation of leather artifacts.